MIFTAHUL JANNAH ORPHANAGE SHARES GOODNESS DURING THE MONTH OF RAMADHAN - Rico Nur Ilham; Irada Sinta; Reza Juanda; Muammar Khaddafi; Muttaqien; Sapna Biby (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This community service article describes a Ramadhan sharing program conducted at Miftahul Jannah Orphanage as a form of social solidarity, faith-based philanthropy, and child-centered community engagement. The program was designed to strengthen care, emotional support, and social connectedness for orphanage children through coordinated assistance, educational reflection, iftar sharing, and interactive engagement with caregivers and volunteers. The method used a descriptive-participatory community service approach consisting of needs identification, program planning, implementation, and reflective evaluation. Data were obtained from field observation, informal dialogue, documentation, and reflection notes. The results indicate that the program contributed to a warmer social atmosphere, improved volunteer awareness of child welfare issues, and strengthened collaboration between the service team and orphanage caregivers. The activity also demonstrated that Ramadhan can become a meaningful moment for integrating charitable giving with educational and psychosocial support. The article recommends that similar programs should be implemented sustainably through needs-based planning, ethical communication with children, and follow-up partnerships rather than one-time ceremonial donation activities.